Polyetylenimine (PEI) adsorption to a DMPG lipid-monolayer in the presence of iron salts and EDTA. (12th October 2016) - Gröning, Andreas; Ahrens, Heiko; Ortmann, Thomas; Lawrenz, Frank; Helm, Christiane A.
Abstract: Branched PEI is adsorbed from 2 mmol/L solution onto a negatively charged DMPG monolayer at the air/water interface from a solution with 2 mmol/L FeSO4 . With X-ray reflectivity it is found that the adsorbed PEI layer contains iron. Compared to PEI adsorbed from clean water the thickness is increased by a factor three to four. It is suggested that cooperative bonds stabilize iron ions within the PEI layer. When the PEI solution contains more EDTA than iron ions, the surface coverage and the thickness of the adsorbed PEI layer is increased by a factor seven. The PEI layer contains electrostatically bound Fe(EDTA) 2− complexes. The thickness and the surface coverage of the adsorbed polymer layer increase when the lipids undergo a phase transition from the liquid expanded (LE) to the liquid condensed (LC) phase. The LC phase is characterized with Grazing Incidence X-ray Diffraction (GIXD). With Brewster Angle Microscopy the formation and growth of LC domains is observed. However, the maximum area fraction of domains is 65%. If the monolayer is highly compressed, we conclude that Brewster Angle Microscopy images a laterally inhomogeneous polymer layer. Graphical abstract: Highlights: PEI adsorption shifts LE/LC phase transition of DMPG to larger surface pressures. Adsorption of Fe(II)SO4 solidifies DMPG monolayer (tilt angle = 0 in LC phase). PEI layers adsorbed from a solution with Fe(II)SO4 or [Fe(EDTA)] 2− -complexes are thick (9–15 nm). Formation of laterally inhomogeneous PEI layer (μm-scale) by monolayer compression into LC phase.